Comparative Transcriptome and Weighted Gene Co-Expression Network Analysis of Eggplant (Solanum melongena L.) Reveals Key Genes Responding to Ralstonia solanacearum Infection - Chuying Yu; Weiliu Li; Rui Xiang; Qihong Yang; Yaqin Jiang; Guiyun Gan; Liangyu Cai; Wenjia Li; Yikui Wang (Agronomy)
Eggplant (Solanum melongena L.) is a widely cultivated vegetable belonging to the family Solanaceae. However, it is highly susceptible to yield reduction owing to soil-borne diseases caused by bacterial wilt (BW) (Ralstonia solanacearum L.). Therefore, understanding the mechanism of bacterial wilt resistance in eggplant is helpful for genetic improvement to create cultivars with strong bacterial wilt resistance. In this study, we conducted a comparative analysis of transcriptomics from eggplant varieties of different genotypes following infection with R. solanacearum. Transcriptome analysis revealed the majority of differentially expressed genes (DEGs) primarily implicated in pathways such as the MAPK signaling pathway, plant hormone signal transduction, and plant–pathogen interactions, as determined using Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. The expression profiles of hormone pathway genes suggest that salicylic acid, ethylene, and jasmonic acid may play significant roles in conferring bacterial wilt resistance. DEGs from the leaves, roots, and stems were partitioned into 14 modules. Among these, the black module exhibited the strongest correlation with target traits and 16 hub genes were identified using gene co-expression network analysis. Subsequently, seven hub genes were selected for validation using RT-qPCR, and the results were consistent with the RNA-seq data. Notably, upon gene annotation, a significant proportion of the hub genes were annotated as heat shock proteins (HSPs) or heat shock transcription factors (HSFs). These findings offer valuable insights for advancing research on the molecular genetic mechanisms through which HSPs/HSFs contribute to bacterial wilt resistance in eggplant.